The Kamala Switch - Dasgupta, Sunil; Schaller, Tom (I Hate Politics Podcasts, 2024)
Episode · I Hate Politics Podcast · The tenth-hour switch to bring in Kamala Harris as the presidential candidate was a breathtaking power play by the Democratic Party. In contrast, the Republican Party has been unable to remove Donald Trump even when party leaders have said that the former president is a threat to the party. Sunil Dasgupta talks with UMBC Political Science Professor Tom Schaller about the role of political parties in this moment. Music for this episode comes from Alexandria, Virginia, alt-rock band, Jackie and The Treehorns.
Keywords: I Hate Politics